Nissen's fundoplication by abdominal approach. Postoperative gastric perforation. - Corradi, Daniel; Lanza, Mario; Delgado, Bolívar (Cirugía del Uruguay, 1983)
... They present a sliding hiatal hernia corrected by a Nissen's fundoplication performed by abdominal approach complicated with a gastro-pleural fistula of fatal evolution. The frequency rate and probable causes are analyzed.